Passivation solution and preparation method and application thereof
By using a passivation solution containing water-soluble resin, trivalent chromium salt, oxalic acid and other components in the aluminum-plastic film, the passivation film layer in the aluminum-plastic film is solved. The problem of poor matching with the inner layer material has achieved better bonding effect and practical life of lithium batteries.
Patent Information
- Application Number
- CN202310127484.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-02-17
AI Technical Summary
During the passivation process of aluminum foil in the existing trivalent chromium passivation liquid, the passivation film formed has poor matching with the inner adhesive and polypropylene film, resulting in poor bonding effect and affecting lithium. The battery's useful life.
A passivation liquid is provided, which consists of a water-soluble resin, trivalent chromium salt, oxalic acid, reactive surfactant, defoaming agent and water. Through the combination of these components, the passivation film layer formed can be combined with the inner layer. The adhesive and polypropylene film are well matched to improve the bonding effect.
After the aluminum foil is passivated by the passivation liquid, the passivation film layer formed has a good matching ability with the inner adhesive and the polypropylene film, and has a good bonding effect, which can effectively improve the practical life of the lithium battery.
Smart Images

Figure CN116334611B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery packaging technology, and in particular to a passivation solution and a preparation method and application thereof. Background Art
[0002] As electronic products become lighter and lighter, lithium batteries also need to develop in the direction of lightweight and high energy density. Soft packaging is an important means of lightweighting lithium batteries. At present, the packaging material used for soft-pack lithium batteries is aluminum-plastic film, which includes nylon film, aluminum foil and cast polypropylene film, and is bonded by adhesive.
[0003] In soft-pack lithium batteries, the liquid electrolyte will directly contact the aluminum-plastic film, and swell and penetrate the polypropylene film to contact the aluminum foil. The common electrolyte composition is a carbonate lithium hexafluorophosphate solution. When water vapor penetrates into the electrolyte solution, the lithium hexafluorophosphate in the electrolyte solution will hydrolyze and produce hydrofluoric acid, which will corrode the aluminum foil and cause bonding failure. Therefore, in order to make the aluminum-plastic film have good corrosion resistance, the aluminum foil in the aluminum-plastic film must be passivated with a passivation liquid. After passivation treatment with a passivation liquid, a dense passivation film will be formed on the surface of the aluminum foil. The passivation film has excellent corrosion resistance and can effectively avoid the above problems.
[0004] The most traditional passivation solution is hexavalent chromium passivation solution, which has a good passivation effect, but hexavalent chromium is highly toxic and is gradually banned. Although the chromium-free passivation solution on the market can meet environmental protection requirements, its comprehensive performance is still far from practical requirements. The toxicity of trivalent chromium is nearly 100 times less than that of hexavalent chromium, and the comprehensive performance of the passivation film it forms is significantly better than that of chromium-free passivation solution, so the market prospect of trivalent chromium passivation solution is broader.
[0005] However, the trivalent chromium passivation solution commonly used for aluminum foil passivation is mainly suitable for ordinary aluminum and its alloys and other metal parts. The passivation film layer formed by it does not match well with the inner adhesive of the aluminum-plastic film and the polypropylene film, and is not suitable for the passivation requirements of the aluminum foil in the aluminum-plastic film. Although there are a few passivation solutions for aluminum foil in aluminum-plastic film, the adhesion between the passivation film layer formed and the inner adhesive and polypropylene film is poor, which can easily reduce the practical life of lithium batteries. Summary of the invention
[0006] Based on this, it is necessary to provide a passivation liquid and its preparation method and application which can improve the bonding effect between the passivation film layer and the inner adhesive layer and the polypropylene film and is suitable for the passivation of aluminum foil in aluminum-plastic film.
[0007] An embodiment of the present application provides a passivation solution, the components of which include a water-soluble resin, a trivalent chromium salt, oxalic acid, a reactive surfactant, a defoaming agent, and water; the structural formula of the water-soluble resin is as follows:
[0008]
[0009] wherein n is independently an integer of 9 to 20, and x is an integer of 1 to 9.
[0010] In one embodiment, the passivation solution comprises the following components by mass percentage:
[0011]
[0012]
[0013] In the aqueous solution of the water-soluble resin, the mass concentration of the water-soluble resin is 25% to 35%.
[0014] In one embodiment, the water-soluble resin is obtained by comprising the following steps:
[0015] Dissolve polyethylene glycol and glutaraldehyde in water and heat to react;
[0016] Optionally, the molecular weight of the polyethylene glycol is 400 to 900;
[0017] Optionally, the molar ratio of the polyethylene glycol to the glutaraldehyde is (0.5-1.0):1;
[0018] Optionally, the temperature of the heating reaction is 75°C to 85°C.
[0019] In one embodiment, the aqueous solution of the water-soluble resin is obtained by the following steps:
[0020] Polyethylene glycol and glutaraldehyde are first mixed to form a mixture, and then the mixture is added into water to prepare an aqueous solution with a mass concentration of 25% to 35% of the mixture, and heated to react to obtain an aqueous solution of the water-soluble resin with a mass concentration of 25% to 35%.
[0021] In one embodiment, the trivalent chromium salt includes one or more of chromium nitrate, chromium sulfate, chromium trichloride and chromium formate.
[0022] In one embodiment, the reactive surfactant includes one or more of polyoxyethylene alkylamine, polyethylene glycol monoallyl ether, and secondary alcohol polyoxyethylene ether having 12 to 14 carbon atoms.
[0023] In one embodiment, the defoaming agent includes one or more of a silicone defoaming agent and a polyether defoaming agent.
[0024] An embodiment of the present application further provides a method for preparing a passivation solution as described in any of the above embodiments, comprising the following steps:
[0025] The components are mixed.
[0026] An embodiment of the present application also provides an aluminum material passivation method, comprising the following steps:
[0027] The aluminum material is passivated using the passivation solution described in any of the above embodiments.
[0028] An embodiment of the present application also provides a method for manufacturing an aluminum-plastic film, comprising the following steps:
[0029] First, the two surfaces of the aluminum foil are passivated by using the passivation solution described in any of the above embodiments to form a passivation film layer;
[0030] Then, a nylon film is bonded on the passivation film layer on one of the surfaces, and a polypropylene film is bonded on the passivation film layer on the other surface to form an aluminum-plastic film semi-finished product;
[0031] The aluminum-plastic film semi-finished product is cured.
[0032] In one embodiment, the adhesive used to bond the nylon film is a polyurethane adhesive, and the adhesive used to bond the polypropylene film is a polyolefin adhesive;
[0033] Optionally, the polyolefin adhesive is an acid-modified polyolefin adhesive;
[0034] Optionally, the polypropylene film is a cast polypropylene film.
[0035] An embodiment of the present application further provides an aluminum-plastic film, characterized in that it is manufactured by the aluminum-plastic film manufacturing method described in any of the above embodiments.
[0036] An embodiment of the present application further provides a lithium battery, characterized in that the aluminum-plastic film as described in the above embodiment is used for cell packaging.
[0037] An embodiment of the present application further provides an electronic product, characterized in that it includes a lithium battery as described in any of the above embodiments.
[0038] The composition of the passivation solution provided by the present application includes a water-soluble resin, a trivalent chromium salt, oxalic acid, a reactive surfactant, a defoamer and water. The water-soluble resin can form a dense passivation film on the surface of the aluminum foil through passivation, and its residual aldehyde group and hydroxyl group can also react with the active groups such as isocyanate and maleic anhydride in the inner layer adhesive at a lower temperature to improve the bonding strength with the adhesive layer; oxalic acid can adjust the pH to reach a suitable aluminum foil corrosion rate, and complex trivalent chromium, and work with the water-soluble resin and reactive surfactant to form a corrosion-resistant passivation film. After the aluminum foil is passivated using the above passivation solution, the formed passivation film layer has good matching with the inner layer adhesive and the polypropylene film, and has a good bonding effect, which is suitable for the passivation of aluminum foil in aluminum-plastic film. DETAILED DESCRIPTION
[0039] For ease of understanding of the application, the application is described more fully below in conjunction with embodiments. The application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0041] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0042] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0043] An embodiment of the present application provides a passivation solution, the components of which include a water-soluble resin, a trivalent chromium salt, oxalic acid, a reactive surfactant, a defoaming agent, and water; the structural formula of the water-soluble resin is as follows:
[0044]
[0045] wherein n is independently an integer of 9 to 20, and x is an integer of 1 to 9.
[0046] The composition of the passivation solution provided by the present application includes a water-soluble resin, a trivalent chromium salt, oxalic acid, a reactive surfactant, a defoamer and water. The water-soluble resin can form a dense passivation film on the surface of the aluminum foil through passivation, and its residual aldehyde group and hydroxyl group can also react with the active groups such as isocyanate and maleic anhydride in the inner layer adhesive at a lower temperature to improve the bonding strength with the adhesive layer; oxalic acid can adjust the pH to reach a suitable aluminum foil corrosion rate, and complex trivalent chromium, and work with the water-soluble resin and reactive surfactant to form a corrosion-resistant passivation film. After the aluminum foil is passivated using the above passivation solution, the formed passivation film layer has good matching with the inner layer adhesive and the polypropylene film, and has a good bonding effect, which is suitable for the passivation of aluminum foil in aluminum-plastic film.
[0047] In one embodiment, the passivation solution comprises the following components by mass percentage:
[0048]
[0049] In the aqueous solution of the water-soluble resin, the mass concentration of the water-soluble resin is 25% to 35%.
[0050] After the water-soluble resin is formulated into an aqueous solution with a mass concentration of 25% to 35%, it is mixed with other components to prepare a passivation solution. The preparation method is simpler and more convenient. The components in the passivation solution are more easily dispersed and uniform, not easy to agglomerate, and have better film-forming properties. It can be understood that in the aqueous solution of the water-soluble resin, the mass concentration of the water-soluble resin can be, for example, but not limited to, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, etc. Preferably, in the aqueous solution of the water-soluble resin, the mass concentration of the water-soluble resin is 28% to 32%. Further preferably, in the aqueous solution of the water-soluble resin, the mass concentration of the water-soluble resin is 30%.
[0051] Furthermore, by controlling the mass percentages of components such as the aqueous solution of the water-soluble resin, trivalent chromium salt, oxalic acid, reactive surfactant, and defoaming agent within a specific range, it is possible to ensure that the passivation solution can form a dense passivation film on the surface of the aluminum foil while also controlling the thickness of the passivation film layer within an appropriate range, thereby avoiding adverse effects on subsequent bonding processes.
[0052] In one embodiment, the water-soluble resin is obtained by comprising the following steps:
[0053] Dissolve polyethylene glycol and glutaraldehyde in water and heat to react.
[0054] Optionally, the molecular weight of polyethylene glycol is 400 to 900. When the molecular weight of polyethylene glycol is within this range, the water-soluble resin can have a suitable crosslinking degree and reduce the occurrence of undesirable phenomena such as agglomeration. It can be understood that the molecular weight of polyethylene glycol can be, for example, but not limited to, 400, 500, 600, 700, 800, 900, etc.
[0055] Optionally, the molar ratio of polyethylene glycol to glutaraldehyde is (0.5-1.0):1. Controlling the molar ratio of polyethylene glycol to glutaraldehyde can make the ratio of aldehyde group and hydroxyl group in the molecular structure of the water-soluble resin appropriate, which is more conducive to improving the bonding ability between the passivation film layer and the inner adhesive layer. It can be understood that the molar ratio of polyethylene glycol to glutaraldehyde can be, for example, but not limited to, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc.
[0056] Optionally, the temperature of the heating reaction is 75° C. to 85° C. It is understandable that the temperature of the heating reaction can be, for example but not limited to, 75° C., 76° C., 77° C., 78° C., 79° C., 80° C., 81° C., 82° C., 83° C., 84° C., 85° C., etc. Preferably, the reaction temperature is 80° C.
[0057] Optionally, the heating reaction time is 3 hours to 5 hours. It can be understood that the heating reaction time can be, for example but not limited to, 3 hours, 4 hours, 5 hours, etc. Preferably, the heating reaction time is 4 hours.
[0058] In one embodiment, the aqueous solution of the water-soluble resin is obtained by the following steps:
[0059] Polyethylene glycol and glutaraldehyde are first mixed to form a mixture, and then the mixture is added into water to prepare an aqueous solution with a mass concentration of 25% to 35% of the mixture, and heated to react to obtain an aqueous solution of a water-soluble resin with a mass concentration of 25% to 35%.
[0060] In one embodiment, the trivalent chromium salt includes one or more of chromium nitrate, chromium sulfate, chromium trichloride and chromium formate.
[0061] In one embodiment, the reactive surfactant includes one or more of polyoxyethylene alkylamine, polyethylene glycol monoallyl ether, and secondary alcohol polyoxyethylene ether having 12 to 14 carbon atoms.
[0062] In one embodiment, the defoaming agent includes one or more of a silicone defoaming agent and a polyether defoaming agent.
[0063] An embodiment of the present application further provides a method for preparing a passivation solution as in any of the above embodiments, comprising the following steps:
[0064] The components were mixed.
[0065] In one embodiment, the process further includes cooling and filtering steps.
[0066] An embodiment of the present application also provides a method for passivating an aluminum material, comprising the following steps:
[0067] The aluminum material is passivated using the passivation solution in any of the above embodiments.
[0068] It can be understood that the passivation solution provided in the present application is suitable for passivation of aluminum materials of various shapes, wherein the shape of the aluminum material can be, for example, foil, strip, tube, plate, etc., but is not limited thereto.
[0069] An embodiment of the present application also provides a method for manufacturing an aluminum-plastic film, comprising the following steps:
[0070] First, the two surfaces of the aluminum foil are passivated by using the passivation solution in any of the above embodiments to form a passivation film layer;
[0071] Then, a nylon film is bonded on the passivation film layer on one surface, and a polypropylene film is bonded on the passivation film layer on the other surface to form an aluminum-plastic film semi-finished product;
[0072] The aluminum-plastic film semi-finished product is cured.
[0073] In one embodiment, the passivation conditions include: wet film thickness 6 μm to 8 μm, temperature 200° C. to 220° C., and time 20 s to 40 s.
[0074] In one embodiment, the adhesive used to bond the nylon film is a polyurethane adhesive, and the adhesive used to bond the polypropylene film is a polyolefin adhesive.
[0075] Optionally, the polyolefin adhesive is an acid-modified polyolefin adhesive. Optionally, the acid-modified polyolefin adhesive may be, for example but not limited to, a maleic anhydride-modified polyolefin adhesive.
[0076] Optionally, the polypropylene film is a cast polypropylene film.
[0077] It is understandable that one surface of the aluminum foil may be passivated first, and then bonded with the nylon film or the polypropylene film, and then the other surface of the aluminum foil may be passivated, and then bonded with the other of the nylon film or the polypropylene film.
[0078] It can be understood that, for example, one of the two surfaces of the aluminum foil can be a matte surface for bonding to the nylon film, and the other surface can be a glossy surface for bonding to the polypropylene film.
[0079] In one embodiment, the aging conditions are: temperature 30°C to 50°C, and time 2 to 4 days.
[0080] An embodiment of the present application further provides an aluminum-plastic film, which is manufactured by the aluminum-plastic film manufacturing method in any of the above embodiments.
[0081] In the above aluminum-plastic film, after the passivation liquid is coated on both surfaces of the aluminum foil, a dense passivation film can be formed on the surface of the aluminum foil, and the film thickness is uniform and the stability is good. After the inner layer adhesive is coated, the passivation film and the inner layer adhesive can form a good bonding force. After the polypropylene film or nylon film is attached, each film layer is firmly bonded and not easy to fall off. The above aluminum-plastic film has good resistance to electrolyte corrosion and can effectively improve the practical life of lithium batteries.
[0082] An embodiment of the present application further provides a lithium battery, which uses the aluminum-plastic film in the above embodiment for cell packaging.
[0083] An embodiment of the present application further provides an electronic product, comprising the lithium battery in the above embodiment.
[0084] The following is a further detailed description of the passivation solution of the present application and its preparation method and application in conjunction with specific examples and comparative examples. It is understandable that in the specific examples, unless otherwise specified, all raw materials can be derived from common commercial sources or can be prepared by known methods. The experimental methods for which specific conditions are not specified in the examples are implemented according to conventional conditions, such as the conditions described in the literature, books, or methods recommended by the manufacturer.
[0085] Example 1
[0086] 1. Preparation of water-soluble resin solution:
[0087] Polyethylene glycol (molecular weight of 400) and glutaraldehyde are weighed and mixed in a molar ratio of 0.5:1 to form a mixture, and the mixture is added into a certain amount of deionized water to prepare a mixture solution with a mixture mass concentration of 30%, and the mixture solution with a mass concentration of 30% is added into a reactor and stirred, heated to 80°C and maintained for 4 hours, and then cooled for standby use, and the obtained resin solution with a solid content and a mass concentration of 30% is a water-soluble resin solution containing aldehyde groups and hydroxyl groups.
[0088] 2. Preparation of passivation solution:
[0089] At room temperature and pressure, add 2% by mass of the water-soluble resin solution prepared in step 1 above into a batching tank. Under stirring conditions, add 2% by mass of chromium nitrate, 0.1% of oxalic acid, 0.02% of C12-14 secondary alcohol polyoxyethylene ether, 0.001% of organosilicon defoamer and 95.879% of pure water in sequence; stir until completely dissolved and uniform, place to cool, and filter the clear solution obtained as the passivation solution.
[0090] 3. Making aluminum plastic film
[0091] Take a 40 μm 8079 aluminum foil, use a wire rod with a wet film thickness of 6.9 μm to first apply the passivation solution prepared in step 2 on the matte surface of the aluminum foil bonded to the nylon film, and take it out after drying in an oven at 210°C for 30 seconds to form a first passivation film layer, use a wire rod with a wet film thickness of 6.9 μm to apply a polyurethane adhesive on the surface of the first passivation film layer, dry it in an oven at 190°C for 30 seconds and then take it out, bond the nylon film, the bonding pressure is 0.5 MPa, and the bonding roller temperature is 90°C;
[0092] The passivation solution prepared in step 2 is coated on the smooth surface of the aluminum foil bonded with the cast polypropylene film with a wire rod having a wet film thickness of 6.9 μm, and the second passivation film layer is formed after being dried in an oven at 210° C. for 30 seconds, and a modified polyolefin adhesive is coated on the surface of the second passivation film layer with a wire rod having a wet film thickness of 6.9 μm, and the second passivation film layer is dried in an oven at 190° C. for 30 seconds and then taken out, and the cast polypropylene film is bonded, the bonding pressure is 0.5 MPa, and the bonding roller temperature is 90° C., to form an aluminum-plastic film semi-finished product;
[0093] The aluminum-plastic film semi-finished product was placed in a 40°C oven for 3 days of curing.
[0094] Example 2
[0095] 1. Preparation of water-soluble resin solution:
[0096] Polyethylene glycol (molecular weight of 600) and glutaraldehyde are weighed and mixed in a molar ratio of 0.8:1 to form a mixture, and the mixture is added into a certain amount of deionized water to prepare a mixture solution with a mixture mass concentration of 30%, and the mixture solution with a mass concentration of 30% is added into a reaction kettle and stirred, heated to 80°C and maintained for 4 hours, and then cooled for standby use, and the obtained resin solution with a solid content and a mass concentration of 30% is a water-soluble resin solution containing aldehyde groups and hydroxyl groups.
[0097] 2. Preparation of passivation solution:
[0098] At room temperature and pressure, add 7% by mass of the water-soluble resin solution prepared in step 1 above into a batching tank. Under stirring conditions, add 6% by mass of chromium sulfate, 1.1% by mass of oxalic acid, 0.04% by mass of polyethylene glycol monoallyl ether, 0.001% by mass of an organosilicon defoamer, and 85.859% by mass of pure water in sequence; stir until completely dissolved and uniformly dissolved, place to cool, and filter the clear solution obtained as the passivation solution.
[0099] 3. Making aluminum plastic film
[0100] Same as step 3 of Example 1.
[0101] Example 3
[0102] 1. Preparation of water-soluble resin solution:
[0103] Polyethylene glycol (molecular weight of 900) and glutaraldehyde are weighed and mixed in a molar ratio of 1:1 to form a mixture, and the mixture is added into a certain amount of deionized water to prepare a mixture solution with a mixture mass concentration of 30%, and the mixture solution with a mass concentration of 30% is added into a reactor and stirred, heated to 80°C and maintained for 4 hours, and then cooled for standby use, and the obtained resin solution with a solid content and a mass concentration of 30% is a water-soluble resin solution containing aldehyde groups and hydroxyl groups.
[0104] 2. Preparation of passivation solution:
[0105] At room temperature and pressure, add 10% by mass of the water-soluble resin solution prepared in step 1 above into a batching tank. Under stirring conditions, add 10% by mass of chromium trichloride, 2% of oxalic acid, 0.05% of polyoxyethylene alkylamine, 0.001% of polyether defoamer and 77.949% of pure water in sequence; stir until completely dissolved and uniform, place to cool, and filter the clear solution obtained as the passivation solution.
[0106] 3. Making aluminum plastic film
[0107] Same as step 3 of Example 1.
[0108] Example 4
[0109] 1. Preparation of water-soluble resin solution:
[0110] Polyethylene glycol (molecular weight of 500) and glutaraldehyde are weighed and mixed in a molar ratio of 0.8:1 to form a mixture, and the mixture is added into a certain amount of deionized water to prepare a mixture solution with a mixture mass concentration of 30%, and the mixture solution with a mass concentration of 30% is added into a reactor and stirred, heated to 80°C and maintained for 4 hours, and then cooled for standby use, and the obtained resin solution with a solid content and a mass concentration of 30% is a water-soluble resin solution containing aldehyde groups and hydroxyl groups.
[0111] 2. Preparation of passivation solution:
[0112] At room temperature and pressure, add 5% by mass of the water-soluble resin solution prepared in step 1 above into a batching tank. Under stirring conditions, add 4% by mass of chromium formate, 0.6% by mass of oxalic acid, 0.03% by mass of polyoxyethylene alkylamine, 0.001% by mass of an organosilicon defoamer and 90.369% by mass of pure water in sequence; stir until completely dissolved and uniformly dissolved, place to cool, and filter the clear solution obtained as the passivation solution.
[0113] 3. Making aluminum plastic film
[0114] Same as step 3 of Example 1.
[0115] Comparative Example 1
[0116] Prepare aluminum-plastic film according to the conventional method:
[0117] Take a 40 μm 8079 aluminum foil, use a wire rod with a wet film thickness of 6.9 μm to coat the matte surface of the aluminum foil to be bonded to the nylon film with a polyurethane adhesive, dry it in an oven at 190°C for 30 seconds, take it out, and bond it to the nylon film. The bonding pressure is 0.5 MPa, and the bonding roller temperature is 90°C.
[0118] The modified polyolefin adhesive was applied to the smooth surface of the aluminum foil bonded with the cast polypropylene film using a wire rod with a wet film thickness of 6.9 μm, and the aluminum foil was dried in an oven at 190° C. for 30 seconds and then taken out and bonded with the cast polypropylene film at a bonding pressure of 0.5 MPa and a bonding roller temperature of 90° C. to form an aluminum-plastic film semi-finished product;
[0119] The aluminum-plastic film semi-finished product was placed in a 40°C oven for 3 days of curing.
[0120] The aluminum-plastic films prepared in Examples 1 to 4 and Comparative Example 1 were subjected to a peeling force test, and the test method was as follows:
[0121] (1) Cut the aluminum-plastic film into sample strips of 200 mm × 15 mm;
[0122] (2) The sample strips were immersed in a mixed solution of ethylene carbonate / dimethyl carbonate / diethyl carbonate (wherein the molar ratio of ethylene carbonate, dimethyl carbonate and diethyl carbonate is 1:1:1) containing 2000 ppm water and 1 mol / L lithium hexafluorophosphate at 85°C, and the change trend of the T-type peel force at different immersion days was tested to characterize its resistance to electrolyte corrosion; T-type peel force test conditions: room temperature, peeling rate 300 mm / min.
[0123] The test results are shown in Table 1 below.
[0124] Table 1 Peel force test results of aluminum-plastic film after different immersion days
[0125]
[0126]
[0127] As can be seen from Table 1, compared with Comparative Example 1, after immersion for 15 days, the aluminum foil and the polypropylene film in the aluminum-plastic films of Examples 1 to 4 still have good adhesion and are not easy to fall off, indicating that the aluminum-plastic films of Examples 1 to 4 have better electrolyte corrosion resistance. Even after immersion in the electrolyte for 15 days, the adhesion between the aluminum foil and the polypropylene film in the aluminum-plastic films of Examples 1 to 4 is only reduced by 1.54% at most, and the adhesion change is small, which can fully meet the requirements of the practical life of lithium batteries.
[0128] The technical features of the above embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0129] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the inventive concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A passivation solution, characterized in that: The components include water-soluble resin, trivalent chromium salt, oxalic acid, reactive surfactant, defoamer and water; the structural formula of the water-soluble resin is as follows: wherein n is independently an integer from 9 to 20, and x is an integer from 1 to 9; The passivation solution comprises the following components by mass percentage: In the aqueous solution of the water-soluble resin, the mass concentration of the water-soluble resin is 25% to 35%; The reactive surfactant includes one or more of polyoxyethylene alkylamine, polyethylene glycol monoallyl ether and secondary alcohol polyoxyethylene ether with 12 to 14 carbon atoms.
2. The passivation solution according to claim 1, characterized in that: The water-soluble resin is obtained by comprising the following steps: Dissolve polyethylene glycol and glutaraldehyde in water and heat to react; The molecular weight of the polyethylene glycol is 400 to 900; The molar ratio of the polyethylene glycol to the glutaraldehyde is (0.5-1.0):1; The temperature of the heating reaction is 75°C to 85°C.
3. The passivation solution according to claim 1, characterized in that: The aqueous solution of the water-soluble resin is obtained by comprising the following steps: Polyethylene glycol and glutaraldehyde are first mixed to form a mixture, and then the mixture is added into water to prepare an aqueous solution with a mass concentration of 25% to 35% of the mixture, and heated to react to obtain an aqueous solution of the water-soluble resin with a mass concentration of 25% to 35%.
4. The passivation solution according to any one of claims 1 to 3, characterized in that: The trivalent chromium salt includes one or more of chromium nitrate, chromium sulfate, chromium trichloride and chromium formate.
5. The passivation solution according to any one of claims 1 to 3, characterized in that: The defoaming agent includes one or more of an organosilicon defoaming agent and a polyether defoaming agent.
6. A method for preparing a passivation solution as claimed in any one of claims 1 to 5, characterized in that: The steps include: The components are mixed.
7. A method for passivation of aluminum material, characterized in that: The steps include: The aluminum material is passivated using the passivation solution as described in any one of claims 1 to 5.
8. A method for making an aluminum-plastic film, characterized in that: The steps include: First, the two surfaces of the aluminum foil are passivated by using the passivation solution as described in any one of claims 1 to 5 to form a passivation film layer; Then, a nylon film is bonded on the passivation film layer on one of the surfaces, and a polypropylene film is bonded on the passivation film layer on the other surface to form an aluminum-plastic film semi-finished product; The aluminum-plastic film semi-finished product is cured.
9. The method for making an aluminum-plastic film according to claim 8, characterized in that: The adhesive used to bond the nylon film is a polyurethane adhesive, and the adhesive used to bond the polypropylene film is a polyolefin adhesive.
10. The method for making an aluminum-plastic film according to claim 9, characterized in that: One or more of the following conditions are met: (1) The polyolefin adhesive is an acid-modified polyolefin adhesive; (2) The polypropylene film is a cast polypropylene film.
11. An aluminum-plastic film, characterized in that: The aluminum-plastic film is produced by the method for producing the aluminum-plastic film according to any one of claims 8 to 10.
12. A lithium battery, characterized in that: The aluminum-plastic film as claimed in claim 11 is used for cell packaging.
13. An electronic product, characterized in that: Comprising the lithium battery as claimed in claim 12.
Citation Information
Patent Citations
Corrosion-resistant coating for active metals
US20110070429A1
Aluminum plastic film for encapsulating lithium battery and aluminum foil passivating process for aluminum plastic film
WO2020118794A1